Meet the expert : Thorr Giddings on .NET modernization techniques & tooling on AWS. - Thorr Giddings, presenter; Shannon Cutt, host (O'Reilly Media, Inc., 2021)
To take full advantage of cloud economics, organizations are modernizing their Windows workloads using a combination of rehosting, replatforming, and refactoring approaches. This unlocks innovation for businesses and delivers new functionality to their customers. As a .NET developer, you're likely seeking options for modernizing your existing .NET Framework applications by analyzing .NET applications, their process dependencies, and technical complexities; porting .NET Framework to .NET Core on Linux; and moving to Windows containers--all in a modern and resilient way that can run anywhere. So what's the best way forward? In this edition of Meet the Expert, Thorr Giddings teaches you how to approach and run a refactoring and replatforming strategy to accelerate innovation, lower TCO, and increase developer productivity for your organization. If you've been tasked with evaluating the modernization of Windows applications, this information-packed hour will highlight a number of modernization pathways and tools that you can leverage on AWS to accelerate your modernization journey. Recorded on November 16, 2021. See the original event page for resources for further learning or watch recordings of other past events. O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.